Handbook on advanced design and manufacturing technologies for biomedical devices - Lantada, Andres Diaz (Springer US, 2013)
The last decades have seen remarkable advances in computer-aided design, engineering and manufacturing technologies, multi-variable simulation tools, medical imaging, biomimetic design, rapid prototyping, micro and nanomanufacturing methods and information management resources, all of which provide new horizons for the Biomedical Engineering fields and the Medical Device Industry. Handbook on Advanced Design and Manufacturing Technologies for Biomedical Devices covers such topics in depth, with an applied perspective and providing several case studies that help to analyze and understand the key factors of the different stages linked to the development of a novel biomedical device, from the conceptual and design steps, to the prototyping and industrialization phases. Main research challenges and future potentials are also discussed, taking into account relevant social demands and a growing market already exceeding billions of dollars. In time, advanced biomedical devices will decisively change methods and results in the medical world, dramatically improving diagnoses and therapies for all kinds of pathologies. But if these biodevices are to fulfill present expectations, today's engineers need a thorough grounding in related simulation, design and manufacturing technologies, and collaboration between experts of different areas has to be promoted, as is also analyzed within this handbook.